The Autonomic Coumel Triangle: A New Way to Define the Fascinating Relationship between Atrial Fibrillation and the Autonomic Nervous System - Marco Rebecchi; Francesca Fanisio; Fabio Rizzi; Alessandro Politano; Ermenegildo De Ruvo; Cinzia Crescenzi; Germana Panattoni; Marianna Squeglia; Annamaria Martino; Stefano Sasso; Paolo Golia; Giulia Pugliese; et al. (Life, 2023)
Arrhythmogenic substrate, modulating factors, and triggering factors (the so-called Coumel’s triangle concept) play a primary role in atrial fibrillation (AF) pathophysiology. Several years have elapsed since Coumel and co-workers advanced the concept of the relevance of autonomic nervous system (ANS) influences on atrial cells’ electrophysiological characteristics. The ANS is not only associated with cardiac rhythm regulation but also exerts an important role in the triggering and maintenance of atrial fibrillation. This review aims to describe in detail the autonomic mechanisms involved in the pathophysiology of atrial fibrillation (AF), starting from the hypothesis of an “Autonomic Coumel Triangle” that stems from the condition of the fundamental role played by the ANS in all phases of the pathophysiology of AF. In this article, we provide updated information on the biomolecular mechanisms of the ANS role in Coumel’s triangle, with the molecular pathways of cardiac autonomic neurotransmission, both adrenergic and cholinergic, and the interplay between the ANS and cardiomyocytes’ action potential. The heterogeneity of the clinical spectrum of the ANS and AF, with the ANS playing a relevant role in situations that may promote the initiation and maintenance of AF, is highlighted. We also report on drug, biological, and gene therapy as well as interventional therapy. On the basis of the evidence reviewed, we propose that one should speak of an “Autonomic Coumel’s Triangle” instead of simply “Coumel’s Triangle”.